Epitelial-to-mesenchimal transition and invasion are upmodulated by tumor-expressed granzyme B and inhibited by docosahexaenoic acid in human colorectal cancer cells. Issue 1 (December 2016) - D'Eliseo, Donatella; Di Rocco, Giuliana; Loria, Rossella; Soddu, Silvia; Santoni, Angela; Velotti, Francesca
Abstract Background Granzyme B (GrB) is a serine protease, traditionally known as expressed by cytotoxic lymphocytes to induce target cell apoptosis. However, it is emerging that GrB, being also produced by a variety of normal and neoplastic cells and potentially acting on multiple targets, might represent a powerful regulator of a wide range of fundamental biological processes. We have previously shown that GrB is expressed in urothelial carcinoma tissues and its expression is associated to both pathological tumor spreading and EMT. We have also shown that docosahexaenoic acid (DHA), a dietary ω-3 polyunsaturated fatty acid with anti-tumor activity, while inhibiting urothelial and pancreatic carcinoma cell invasion also inhibited their GrB expression in vitro. In this study, we characterized a panel of colorectal carcinoma (CRC) cells, with different invasive capabilities, for GrB expression and for the contribution of GrB to their EMT and invasive phenotype. In addition, we investigated the effect of DHA on CRC cell-associated GrB expression, EMT and invasion. Methods The expression levels of GrB and EMT-related markers were evaluated by Western blotting. GrB knockdown was performed by Stealth RNAi small interfering RNA silencing and ectopic GrB expression by transfection of human GrB vector. Cell invasion was determined by the BioCoat Matrigel invasion chamber test. Results GrB was produced in 57.1 % CRC cell lines and 100 % CRC-derived Cancer Stem Cells. Although GrB was constitutive expressed in both invasive and noninvasive CRC cells, GrB depletion in invasive CRC cells downmodulated their invasion in vitro, suggesting a contribution of GrB to CRC invasiveness. GrB loss or gain of function downmodulated or upmodulated EMT, respectively, according to the analysis of cancer cell expression of three EMT biomarkers (Snail1, E-cadherin, N-cadherin). Moreover, TGF-β1-driven EMT was associated to the enhancement of GrB expression in CRC cell lines, and GrB depletion led to downmodulation of TGF-β1-driven EMT. In addition, DHA inhibited GrB expression, EMT and invasion in CRC cells in vitro. Conclusions These findings present a novel role for GrB as upmodulator of EMT in CRC cells. Moreover, these results support the use of DHA, a dietary compound without toxic effects, as adjuvant in CRC therapy.